Genetic Transformation of Plumbago zeylanica with Agrobacterium rhizogenes Strain LBA 9402 and Characterization of Transformed Root Lines - Basu, Amrita; Joshi, Raj Kumar; Jha, Sumita (Plant Tissue Culture and Biotechnology, 2015)
High frequency transformation (73.80 ± 2.24%) has been obtained in Plumbago zeylanica using nodes and internodes of axenic whole plants infected with Agrobacterium rhizogenes strain LBA 9402. The root lines could be distinguished morphologically into two types : Root lines of morphotypes I and II. While morphotype I showed profuse branching with short (< 1 cm), highly dense hairy laterals, the roots of morphotype II roots were characterized also by profuse branching with long hairy laterals (> 3 ? 4 cm). Only four of the ten root lines showed integration of four rol genes (rolA, rolB, rolC and rolD) of TL?DNA. None of the root lines showed presence of any of the five genes of TR?DNA. It is noteworthy that the root morphotypes (I and II) showed a clear distinction in the nature of integration and expression of rol genes. The transformed root lines varied significantly (p ? 0.05) with respect to DW (GI DW basis, 2.19 ± 0.24 ? 5.31 ± 0.6) after 4 weeks of culture on solid modified MS; and plumbagin contents in root lines (4.81 ± 0.16 ? 6.69 ± 0.34 mg/g DW) were higher than that reported earlier. Transformed root lines of P. zeylanica maintained in vitro on phytohormone devoid medium for over 2 years can be used for scale up studies for the production of plumbagin in bioreactors. Plant Tissue Cult. & Biotech. 25(1): 21-35, 2015 (June)